2003
DOI: 10.1016/s0248-4900(03)00009-1
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of two classes of nuclear vesicles is induced by the dissociation of soluble proteins from one class of vesicles

Abstract: The regulatory mechanism of fusion steps in nuclear envelope assembly was studied in vitro using cell-free extracts of Xenopus eggs. The nuclear envelope is formed only around the chromatin at the end of mitosis. Two kinds of vesicles are required for nuclear envelope assembly (J. Cell Biol. 112 (1991) 545). Light vesicles (LVs) have the chromatin-binding activity, but cannot fuse solely. On the other hand, heavy vesicles (HVs) neither bind to the chromatin nor LVs, but are needed for the fusion event. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, we propose that, in mediating NE precursor vesicles to bind to chromatin, LBR may first bind to a linker protein to mediate the membrane-chromatin attachment, as it was reported that the LBR-containing NE precursor vesicles can not bind directly to chromatin at the onset of nuclear assembly (Drummnond et al, 1999;Oke and Inoue, 2003). We propose that this linker protein is importin ␤, which is also very important for NE precursor vesicle recruitment (Zhang et al, 2002b).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, we propose that, in mediating NE precursor vesicles to bind to chromatin, LBR may first bind to a linker protein to mediate the membrane-chromatin attachment, as it was reported that the LBR-containing NE precursor vesicles can not bind directly to chromatin at the onset of nuclear assembly (Drummnond et al, 1999;Oke and Inoue, 2003). We propose that this linker protein is importin ␤, which is also very important for NE precursor vesicle recruitment (Zhang et al, 2002b).…”
Section: Discussionmentioning
confidence: 75%
“…Functionally distinct membrane fractions with chromatin targeting, membrane fusion and NPC-inducing activities have also been described by others (Vigers and Lohka, 1991;Sasagawa et al, 1999;Oke and Inoue, 2003). However, in contrast to our present results, formation of intact NEs with NPCs required the simultaneous presence of these membrane fractions in the nuclear reconstitution assays.…”
Section: Introductionmentioning
confidence: 75%